2013
DOI: 10.1371/journal.pone.0071278
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Disrupting Effects of Alternaria Alternata Extract on Bronchial Epithelium from Asthmatic Donors

Abstract: Sensitization and exposure to the allergenic fungus Alternaria alternata has been associated with increased risk of asthma and asthma exacerbations. The first cells to encounter inhaled allergens are epithelial cells at the airway mucosal surface. Epithelial barrier function has previously been reported to be defective in asthma. This study investigated the contribution of proteases from Alternaria alternata on epithelial barrier function and inflammatory responses and compared responses of in vitro cultures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 58 publications
(62 reference statements)
5
72
0
Order By: Relevance
“…Another report from the Davies lab demonstrated that exposure of 16HBE cells to extracts of the allergenic fungus Alternaria alternata reduced TEER in a dose-dependent manner (e.g. ~50% reduction at 24 hrs using 100 μg/ml), although PBEC from healthy donors appeared to be resistant to these effects 69 . Interestingly, PBEC derived from severe asthmatics were more susceptible to Alternaria -induced reductions in TEER, although this effect was transient and only apparent using high extract concentrations (>100 μg/ml).…”
Section: Models Of Inducible Barrier Dysfunctionmentioning
confidence: 99%
“…Another report from the Davies lab demonstrated that exposure of 16HBE cells to extracts of the allergenic fungus Alternaria alternata reduced TEER in a dose-dependent manner (e.g. ~50% reduction at 24 hrs using 100 μg/ml), although PBEC from healthy donors appeared to be resistant to these effects 69 . Interestingly, PBEC derived from severe asthmatics were more susceptible to Alternaria -induced reductions in TEER, although this effect was transient and only apparent using high extract concentrations (>100 μg/ml).…”
Section: Models Of Inducible Barrier Dysfunctionmentioning
confidence: 99%
“…In these studies the effect of Alternaria alternata extract, which is known to disrupt epithelial barrier integrity, 30 was examined in knob-treated versus untreated 16HBE14o− cells cultured under regular conditions. Although barrier integrity of knob-treated and untreated 16HBE14o− cell cultures was affected by exposure to Alternaria alternata extract, the change in TER of knob-treated 16HBE14o− monolayers was significantly less than that observed in untreated monolayers after 9 hours (Fig 6, C ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, knob could be exerting a protective effect by inhibiting protease activity of Alternaria alternata 30 or suppressing Alternaria alternata –induced matrix metalloprotease secretion, 42 both of which act on epithelial monolayers to decrease TER. 30,43 In contrast to our observations with knob treatment, infection with rhinovirus has been shown to decrease expression of E-cadherin, occludin, and zonula occludens 1 along with a reduction in TER in nasal epithelial cells, 44 as well as in biopsy specimens (transtissue resistance) from patients with chronic rhinosinusitis. 45 Along these lines, infection of 16HBE14o− cells with rhinovirus was shown to result in damage to the respiratory epithelial barrier and facilitate allergen penetration, thus contributing to increased allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lungs of asthmatic subjects with Af sensitivity (positive skin prick test) may be more susceptible to germination of Af spores and have a higher burden of Af recoverable from sputum 41 . Airway epithelium in subjects with asthma may be more susceptible to the permeability-inducing effects of protease allergens than that of healthy controls 11 . Taken together, these results and our work suggest that chronic pulmonary inflammation and epithelial desquamation associated with asthma promote dissemination of allergens such as Alp 1 into the bronchial smooth muscle layer.…”
Section: Discussionmentioning
confidence: 99%